2014
DOI: 10.1021/ic402778x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling the Excited State and Photosensitizing Property of a 2-(2-Pyridyl)benzo[b]thiophene-Based Cationic Iridium Complex through Simple Chemical Modification

Abstract: Bis-cyclometalated cationic iridium (Ir) complexes 1-4 comprising two 2-(2-pyridyl)benzo[b]thiophene (btp) ligands and one 2,2'-bipyridyl (bpy) ancillary ligand with different substituents were prepared as new visible light-absorbing sensitizers and examined for their photophysical and electrochemical properties. Complex 1 was prepared as a parent complex without any substituents. Complexes 2-4 contained methyl-, methoxy-, and trifluoromethyl groups at 4,4'-positions on the bpy ancillary ligand. Systematic inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
61
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 89 publications
5
61
2
Order By: Relevance
“…In contrast to the archetype compounds [Ir-(ppy) 2 (L^L)]PF 6 (ppy = 2-phenylpyridine or 2-(2,4-difluorophenyl)pyridine and L^L = bis-carbene or pyridinecarbene), where the pyridine groups of the cyclometallating ppy ligands are always in trans orientation to each other, 31 in this series we observed cis and trans isomers. In both cases the C(1)−Ir(1)−C (19) angle deviates from linearity with 169.74 (7) 58 On the other hand, the described cathodic shift of 20 mV for the reduction potential was not found in our study. The minor differences in donor strength of the substituents on the 2,2′-bipyridine ligands seem to be overcompensated by the strongly donating carbene groups, resulting in an ∼150 mV cathodic shift of complexes trans-1 and trans-3 when compared to its corresponding 2-(2-pyridyl)benzo[b]thiophene iridium complexes.…”
Section: Inorganic Chemistrycontrasting
confidence: 89%
See 1 more Smart Citation
“…In contrast to the archetype compounds [Ir-(ppy) 2 (L^L)]PF 6 (ppy = 2-phenylpyridine or 2-(2,4-difluorophenyl)pyridine and L^L = bis-carbene or pyridinecarbene), where the pyridine groups of the cyclometallating ppy ligands are always in trans orientation to each other, 31 in this series we observed cis and trans isomers. In both cases the C(1)−Ir(1)−C (19) angle deviates from linearity with 169.74 (7) 58 On the other hand, the described cathodic shift of 20 mV for the reduction potential was not found in our study. The minor differences in donor strength of the substituents on the 2,2′-bipyridine ligands seem to be overcompensated by the strongly donating carbene groups, resulting in an ∼150 mV cathodic shift of complexes trans-1 and trans-3 when compared to its corresponding 2-(2-pyridyl)benzo[b]thiophene iridium complexes.…”
Section: Inorganic Chemistrycontrasting
confidence: 89%
“…The minor differences in donor strength of the substituents on the 2,2′-bipyridine ligands seem to be overcompensated by the strongly donating carbene groups, resulting in an ∼150 mV cathodic shift of complexes trans-1 and trans-3 when compared to its corresponding 2-(2-pyridyl)benzo[b]thiophene iridium complexes. 58 Both, oxidation and reduction processes show excellent reversibility throughout the entire series, as rarely observed for analogous luminescent iridium complexes. High stability can therefore be expected in electroluminescent devices.…”
Section: Inorganic Chemistrymentioning
confidence: 68%
“…Intense absorption bands observed below 365 nm are attributed to the spin-allowed ligand-centered 1 π-π * transitions arising from both the cyclometalated and ancillary ligands. The weaker bands at lower energies (400-600 nm) are assigned to spin-allowed [35][36][37][38]. However, it is found that the electrondonating tert-butyl groups on the bpy ligand of complex 3c cause the absorption maximum red-shift of 10 nm in the latter low-energy region.…”
Section: Electronic Absorption Spectroscopymentioning
confidence: 92%
“…A major drawback of these strategies is that they invariably result in concomitant variation of the emission colour and/or redox potentials of the complexes because of the intimate interplay between chemical structure and properties. [57][58][59] Therefore distinguishing the exact effect of a structural modification on specific properties is still a major challenge.…”
Section: Introductionmentioning
confidence: 99%